2010
DOI: 10.1161/circulationaha.109.911156
|View full text |Cite
|
Sign up to set email alerts
|

Selective Molecular Potassium Channel Blockade Prevents Atrial Fibrillation

Abstract: Background-Safety and efficacy limit currently available atrial fibrillation (AF) therapies. We hypothesized that atrial gene transfer would allow focal manipulation of atrial electrophysiology and, by eliminating reentry, would prevent AF. Methods and Results-In a porcine AF model, we compared control animals to animals receiving adenovirus that encoded KCNH2-G628S, a dominant negative mutant of the I Kr potassium channel ␣-subunit (G628S animals). After epicardial atrial gene transfer and pacemaker implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 37 publications
(37 reference statements)
1
66
1
1
Order By: Relevance
“…A selective small-conductance I KCa channel inhibitor suppresses AF in a range of animal models (144). Still another approach is to use gene transfer to deliver dominant-negative K + channel subunits to selectively prolong atrial APD, which suppresses AF in a porcine model (145).…”
Section: Potential Therapeutic Implicationsmentioning
confidence: 99%
“…A selective small-conductance I KCa channel inhibitor suppresses AF in a range of animal models (144). Still another approach is to use gene transfer to deliver dominant-negative K + channel subunits to selectively prolong atrial APD, which suppresses AF in a porcine model (145).…”
Section: Potential Therapeutic Implicationsmentioning
confidence: 99%
“…KCNH2-G628S successfully delayed the onset of atrial fibrillation. 85 Recently, Bauer et al 77 reported intra-atrial delivery of three different genes employing epicardial electroporation: dominant-negative canine ether-a-go-go-related gene channel mutant CERG-G627S, 86 small interfering RNA caspase3 (ref. 87) and connexin 43.…”
Section: Targeting Electric Dysfunctionmentioning
confidence: 99%
“…98 Another pericardial approach employs a camel hair paintbrush to paint the virus on epicardial surface with trypsin and poloxamer gel. 85 This method was reported to achieve transmural gene transfer to the atrium, without negatively affecting the ventricular myocardium.…”
Section: Pericardial Deliverymentioning
confidence: 99%
“…That study underscores the fact that the pathogenesis of AF and its underlying molecular mechanisms are not completely understood. Recently, a series of preclinical studies suggested that genebased approaches could be used for the diagnosis and treatment of AF [9,10]. Most studies have had encouraging results that indicate the potential of gene-based therapies to combat AF.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have had encouraging results that indicate the potential of gene-based therapies to combat AF. Amit's group utilized an adenoviral-mediated delivery of KCNH2 (negative mutant of the IKr potassium channel) into a porcine AF model to enable epicardial atrial gene transfer and pacemaker implantation, as well as electrophysiological and molecular studies [9]. The authors found that KCNH2 transfer prolonged atrial action potential duration and prevented AF [9].…”
Section: Introductionmentioning
confidence: 99%